Empirical analysis of the consumer behavior and preferences for the health security of tribal population in North East India (International Journal of Food and Nutritional Sciences, 2023)
In the North east states of India, pork is the dominant form (78%) of meat consumption. The study attempts to understand the consumer behaviour and preferences of pork and pork products in selective North East states to know the prospect of pork centric enterprises in the area. An economic analysis of 716 consumers indicated significant differences in pork consumption across age, education and occupation categories. Friedman test revealed a significant difference in the frequency of pork consumption among the states of North East India. Pork preparation, visual attributes and place of buying pork impacted pork consumption decision. Butcheries and street vendors were most favored place of buying pork products. Pork pickle and nuggets was most preferred product. An increased consumption of pork products along with increased demand for greater variety in local pork products by the youth indicates presence of huge untapped market and a prospective scope to increase the income and employment opportunities.